Enhancing nitrogen removal from anaerobically-digested swine wastewater through integration of Myriophyllum aquaticum and free nitrous acid-based technology in a constructed wetland - Zhou, Sining (2022)
Despite of low operation costs and convenient maintenance, the application of natural systems for swine wastewater treatment has been limited by large construction area and unsatisfactory effluent quality. Introducing ammonium high uptake aquatic plants and shifting nitrogen removal pathway from nitrate to nitrite in constructed wetlands (CWs) has been regarded as promising approach to promote their performances. This study aimed to establish nitrite pathway and enhance N removal via free nitrous acid (FNA)-sediment treatment and Myriophyllum aquaticum vegetation in the CWs treating anaerobically digested swine wastewater. Nitrite pathway was successfully and stably achieved in the M. aquaticum CW with FNA-treated sediment. The overall removal efficiencies of ammonium nitrogen and total nitrogen were 42.3 ± 10.2% and 37.7 ± 9.3% in the planted CWs with FNA-treated sediment, which were 76.3% and 65.4% higher than those in the conventional oxidation pond system, respectively. Microbial community analysis (qPCR and metagenomics) suggested that the nitrite pathway established through FNA-sediment treatment was based on the inactivation of nitrite oxidizing bacteria (lower nxrA gene abundance) and the reduction of relative abundances of NOB (especially Nitrobacter and Nitrospira). During the denitrification processes, the integration of M. aquaticum vegetation with FNA-sediment treatment can lower the nitrate reduction by decreasing narG gene abundances and decreasing the relative abundances of napA affiliated bacteria (especially Bradyrhizobium), while strengthening reduction of nitrite and nitrous oxide by increasing nirK and nosZ gene abundances and enriching the corresponding affiliated microbial taxa, Mycobacterium and Bacillus, respectively. Our findings suggest that applying FNA-based technology in CW systems is technically and economically feasible, which holds promise for upgrading current CW systems treating swine wastewater to meet future water quality requirements.